Implementation of corporate social responsibility PT. Angkasa Pura Semarang to improve the community’s economy - Sena, Asykar Habib Tahar; Afendi, Arif (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2022)
Corporate social responsibility (CSR) is a concept or action taken by a company towards the social and environmental aspects in which the company is located. CSR is carried out to establish a healthy relationship between the company and society. This research aims to determine the implementation of PT Angkasa Pura Semarang’s corporate social responsibility (CSR) in improving the community’s economy in Kampoeng Djadoel Semarang. This type of research uses descriptive qualitative research methods by collecting data through observation and interviews. This research’s results indicate the implementation of corporate social responsibility at PT. Angkasa Pura Semarang can improve the economy of the Kampoeng Djadhoel Semarang community through the community development partnership program with a community empowerment-based strategy, so that currently Kampoeng Djadoel has become one of the main tourist destination icons in the city of Semarang. This research proves that the CSR program carried out by PT. Angkasa Pura Semarang can improve the community’s economy through the community development partnership assistance program with a community empowerment-based strategy.